THE PRINCIPLE OF OPERATION OF THE WIND POWER PLANT AND ITS ADVANTAGES ("Conference on Universal Science Research 2023", 2023)
Wind is the movement of air masses as a result of changes in pressure due to the intensity of sunlight. The conversion of mechanical energy generated by air flow into electrical energy is carried out with the help of wind power plants. Wind energy is an environmentally friendly source of energy. Germany ranks first in the use of wind energy.